Force and velocity characteristics of land training devices in swimming - Klauck, J.; Daniel, K. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The specific objectives of this study are the presentation and discussion of mechanical parameters - force, velocity and mechanical power- measured during land training of swimmers performing imitated armstrokes (breastroke or dolphin). The training devices used were stretch cords, an isokinetic mini-gym, and a latissimus machine. Force measurements were made by the means of a strain gauge cell fixed between the traction rope and the hand of the swimmer. The velocity-time curve of the hand was measured by using an ultra-sound Doppler-system. The mechanical power was obtained by analogue multiplication of force and velocity data. The forces measured reached maximal values of 200-300 N, the peak "stroke" velocity of the hand varied between 1 and 4 m/s. Maximum values of the mechanical power up to 500 Y were obtained. It is shown that an imitation of arm strokes in swimming cannot be performed in the force, velocity and time domain simultaneously. Furthermore, the mechanical characteristics of the training devices used yield different time distributions of force and/or velocity and/or mechanical power within the armstroke cycle.